RESIDU ANTIBIOTIK PADA SUSU KAMBING PE YANG MENDERITA MASTITIS SUBKLINIS DI DESA AIKMUAL LOMBOK TENGAH - rodi iskandar (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2020)
Subclinical mastitis is a disease that often occurs in Etawa (PE) crossbreed goat farms. Farmers in handling this disease usually use antibiotics, giving antibiotics that are not right or according to the procedure can cause residues. The presence of antibiotic residues in goat's milk can have an impact on human health such as poisoning, allergies, and microbiological disorders. This study aims to determine the incidence rate and find the presence of antibiotic residues in the milk of Etawa Peranakan goat who suffer from subclinical mastitis in Aikmual Village, Central Lombok Regency. Test results from 6 samples of etawa-crossed goat milk (PE) suffering from subclinical mastitis using the Bioassay Screening Test method showed negative results containing antibiotic residues. Negative results in the sample are marked by the absence of dead bacteria on paper discs that have been soaked with milk samples from goats that are positive for subclinical mastitis, this is evident from the absence of inhibitory zones formed. The negative effect of this milk sample is due to several possibilities, namely: The stopping period of the drug has been reached and the antibiotics used are in accordance with the dose. The duration of the presence of antibiotics in milk depends on several factors, including: dose, method of administration and type of antibiotic. In general, it is applied that the withdrawal time of narrow spectrum antibiotics is at least 5 days after treatment, for the type of antibiotics that can form a depot (broad spectrum) has a withdrawal time of 1 3 days